Impact of Dietary or Drinking Water Ruminococcus sp. Supplementation and/or Heat Stress on Growth, Histopathology, and Bursal Gene Expression of Broilers - Saad, Adel Hassan; Ahmed, Mohamed S.; Aboubakr, Mohamed; Ghoneim, Hanan A.; Abdel-Daim, Mohamed M.; Albadrani, Ghadeer M.; Arafat, Nagah; Fadl, Sabreen Ezzat; Abdo, Walied (Frontiers in Veterinary Science, 2021)
This research was to evaluate the impact of dietary or drinking water Ruminococcus sp. supplementation and/or heat stress (HS) on the growth, serum biochemistry, tissue antioxidant, phagocytic assay, histopathology, and bursa gene expression of broilers. Day-old broiler chicks were allotted into 6 groups according to HS and/or Ruminococcus with or without enzyme supplementation. The first group was the control one with a formulated diet without any supplement and normal environmental temperature. The second group, fed on Ruminococcus (1kg/kg diet) supplemented diet. The third group, fed on a formulated diet without supplement and Ruminococcus and digestive enzymes were given in drinking water (0.1ml/litter). The fourth one was the heat stress group with a normal formulated diet. The fifth and the sixth groups as second and third groups, respectively but with heat stress. Results of this experiment indicated that thermal temperature negatively affected parameters of the growth performance, serum biochemical, tissue antioxidants, and phagocytic assay. Moreover, heat stress led to pathological lesions in the internal organs and affected the expression of some genes related to heat stress including proapoptotic genes as caspase8 and bax, inflammatory genes as NF-κβ1, and heat shock protein as HSP 70 in the bursal tissue. These bad effects and abnormalities were mitigated by Ruminococcus alone or with enzyme supplementation, which improved all the above-mentioned parameters.